Pengembangan Bahan Ajar Suplemen PembelajaranMateri Gempa Bumi Berbasis Elektronik Untuk SiswaKelas Vii Smp - Wicaksono, Damas Gumelar; , Drs,Suharjo,MS (2016)
Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. September, 2016. The development of teknology for an innovative teacher need for innovation in the design developmen of a more interesting teaching material and student were able to achieve the learning objective. This research to objective, that is : (1) Know the criteria electronic teaching materials based supplement earthquake.; (2) Developing electronic teaching materials based supplement electronic materials earthquake class VII.; (3) Knowing improving student learning outcomes using teaching material. This methods of research and developmentn uses Dick & Carey model. This research conducted in SMP N 2 Colomadu for a class VII H totalling 30 Student, with eksperimental design One-Group Pretest posttest and uses strategy discussion to look at improving student learning outcomes using teaching material. This research to produce product such as electrinic-based teacing material (Kvisoft Flip Book Maker), then in eksperimen. Experimen reuslt using the test a Paired Sample T Test by result tabulating the pretest 43% and increase after posttest 57%. The result of an increase in student learning outcomes have an average of 14%. The result show teaching material developed effective researchcers to use in learning. Keywords : Teaching material, development, the result of student study.